Protective Effect of the Hexanic Extract of Eryngium carlinae Inflorescences In Vitro, in Yeast, and in Streptozotocin-Induced Diabetic Male Rats - Peña-Montes, Donovan J. (Antioxidants (Basel), 2019)
In the present study, we investigated the composition and antioxidant activity of the hexanic extract of Eryngium carlinae inflorescences by employing in vitro assays to measure antioxidant capacity and 2,2-diphenyl-1-picrylhydrazyl scavenging activity. We also applied the hexanic extract to Saccharomyces cerevisiae, under hydrogen peroxide-induced stress. Finally, we tested the extract in male Wistar rats with and without streptozotocin-induced diabetes. The compounds in the hexanic extract were analyzed by gas-chromatography-mass spectrometry, which revealed mainly terpenes and sesquiterpenes, including (Z)β-farnesene (38.79%), β-pinene (17.53%), calamene (13.3%), and α-farnesene (10.38%). In vitro and in S. cerevisiae, the extract possessed antioxidant activity at different concentrations, compared to ascorbic acid (positive control). In normoglycemic and hyperglycemic rats, oral administration of 30 mg/kg of the extract reduced blood glucose levels; lipid peroxidation in liver, kidney and brain; protein carbonylation; and reactive oxygen species (ROS) production. It also increased catalase activity in the brain, kidneys and liver. These findings show that this hexanic extract of E. carlinae inflorescences possessed antioxidant properties.